Odpowiedź :
a)
[tex]x + 4 - 5(x - 8) = x - 6 \\ x + 4 - 5x + 40 = x - 6 \\ x - 5x - x = - 6 - 40 - 4 \\ - 5x = - 50 \\ x = 10[/tex]
b)
[tex]6x - (x + 1) = 6 \\ 6x - x - 1 = 6 \\ 6x - x = 6 + 1 \\ 5x = 7 \\ x = \frac{7}{5} = 1 \frac{2}{5} = 1.4[/tex]
c)
[tex]2(x - 1) + 3(x - 2) = 7 \\ 2x - 2 + 3x - 6 = 7 \\ 2x + 3x = 7 + 2 + 6 \\ 5x = 15 \\ x = 3[/tex]
d)
[tex]5(x - 1) + 2x = 2(x + 2) + 6 \\ 5x - 5 + 2x = 2x + 4 + 6 \\ 5x + 2x - 2x = 4 + 6 + 5 \\ 5x = 15 \\ x = 3[/tex]
e)
[tex] \frac{2x - 1}{5} - \frac{x - 2}{2} = \frac{7}{10} x | \times 10 \\ 2(2x - 1) - 5(x - 2) = 7x \\ 4x - 2 - 5x + 10 = 7x \\ 4x - 5x - 7x = 2 - 10 \\ - 8x = - 8 \\ x = 1[/tex]